Sectoral labour market effects of the 2006 FIFA World Cup - Arne Feddersen; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
Using the case of the 2006 FIFA World Cup, this study is the first to test the employment effects of a mega-sporting event on the basis of data that are both regional and sectoral. It is also the first study of sporting events to use a non-parametric test method. Earlier studies on the World Cup could not identify any employment effects. In contrast, we find a small but significant positive em-ployment effect on the hospitality sector and a negative effect on the construction sector. To our knowledge, this is the first time that such a crowding-out effect of public investment on the occasion of a mega-sporting event has been found in an empirical analysis.
Keywords: H54; R12; L83; 330; FIFA; World Cup; Economic Impact; Ex-post Analysis; Sectoral Employment